(3TQM ebGeGJ GdMQjQjs - (3GdNhGQRej GdeWQRj, CHh GdaJM, HQgGf GdOjf, fGUQ Hf YHO GdSjO CHi GdecGQe, J(B610(3g`s ((3eMehO Hf eMeO Hf EHQGgje YhGO chGRj GdTGaYjs)
(3ChdgG (B:s
(3HSe Gddg (B..(3aGfj de CQ aj cJH GdYQHjI hGdCOH hdG aj JUGfja GdYLe hGdYQH cJGHG CMSf JCdjaG hCYLH JUfjaG hCZQH JQUjaG hCTed ddYLGFH GdYQHjI hCLeY ddZQGFH GdCOHjI (B...s
(3BNQgG (B:s
... (3hbhdg hKO YQVJ Ydjg TjFG ef ahGJM cJGH gPG dCf UQJ cTGa GdeTcdGJ EPG GfTQMJ cJGH GdebGeGJ SbGg Gddg TBHjH QVhGfg (B.. (3hbO hbY GdaQGZs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7\348s
(3cTa GdXfhf (B2\1787s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs